Social Basis of Procedural Relations - PONOMARENKOV, Vitaly; KALASHNIKOVA, Elena B.; KOROBOVA, Aleksandra P.; PETROGRATSKAYA, Albina A.; KAREV, Dmitry A. (Journal of Advanced Research in Law and Economics; Vol 9 No 3(33) (2018): JARLE, Volume IX, Issue 3(33), Summer 2018, 2018)
Topicality. Topicality of the studied problem is caused by the fact the legal science pays little attention to social analysis of procedural relations, which leads to emergence of diametrically opposite ideas of the same legal phenomena. This complicates the legislative and law enforcement activities. The purpose of the article is to study social causes and mechanisms of emergence of procedural relations and to form integrated approaches to understanding the sense and contents of procedural relations. The methodological basis of the work consists of the cognitive and systemic and determination approach, which requires using a complex of general scientific, specific scientific, and special methods of cognition. The authors study the social essence of procedural relations that emerge in law enforcement activities and show different regulatory mechanisms of realization of these relations. The history of emergence of the notion of procedural relation is viewed, the main approaches to understanding it are analyzed, and the social component of procedural relations is analyzed in various aspects of its manifestation. Practical significance. The materials of the article pose practical value for researchers who study the problem of procedural law and implement the law enforcement and legislative activities.